Comparative biology of some Cicadulina species and populations from various climatic zones in Nigeria (Hemiptera: Cicadellidae) - Okoth, V.A.O.; Dabrowski, Z.T.; Van Emden, H.F. (1987)
Significant differences in nymphal development period and fecundity were observed between five populations of Cicadulina mbila (Naudé) and C. triangula Ruppel from three climatic zones in Nigeria: rain forest (Ibadan), southern part of Sudan savanna (Kadawa, Kano) and the Jos Plateau. The C. triangula population that is used in mass rearing for resistance screening at the International Institute of Tropical Agriculture (IITA), Ibadan, developed much more rapidly than the wild C. triangula population from Ibadan. Similarly, the C. mbila population from the Kadawa Irrigation Scheme, Kano, developed more rapidly than the population from the Jos Plateau. All Cicadulina populations were 3–4 times as prolific on pearl millet as on maize, sorghum or the grass Digitaria exilis. The IITA colony of C. triangula was significantly more fecund than C. mbila. It is clear that Cicadulina species and populations with high reproductive potential would be most suitable for mass rearing for resistance screening to the maize streak virus disease.